Application of acoustic emission technique to limoges enamels for damage assessment - Jenny Studer (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Tungsten-halide lighting has been found to cause significant temperature distributions within showcases. The risk from such medium scale heating events is not easy to assess; therefore the acoustic emission technique was used to detect micro damage within Limoges enamels, as previous research has shown how vulnerable these enamels are. Prior to applying the technique to the originals, enamel samples were used in flexure tests and exposed to variations of temperature to assess their response to stress induced deterioration. The temperature and relative humidity distribution in two display cases were measured with data loggers at different points to assess the thermal loading. In addition, the performance of current methods to control relative humidity, the air exchange rate, and the risks from carbonyl pollutants within the showcases were also assessed. This analysis resulted in several changes to improve the display microenvironment.